2018
DOI: 10.1002/lipd.12032
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Potential miRNA Involved in Adipogenic Differentiation of C2C12 Myoblasts

Abstract: >Emerging evidence indicates that microRNA (miRNA) plays an important role in adipogenesis and disease pathogenesis. To investigate the miRNA involved in regulating different periods of adipogenesis, we performed a comprehensive study on microRNAome during the stimulation of adipogenesis by an adipogenic differentiation cocktail in C2C12 myoblasts at 0, 2, 4, and 7 days using the Solexa sequencing technology. In this study, we identified 52 differentially expressed (DE) miRNA. Functional annotation indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Accumulating studies have shown that miRNAs are involved in many biological processes 8,40,41 , including skeletal myogenesis 10,16 . In this study, we performed a nonbiased analysis to assess miRNA and mRNA expression as well as ATAC-seq and ChIP-seq to investigate chromatin accessibility and TF occupancies, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have shown that miRNAs are involved in many biological processes 8,40,41 , including skeletal myogenesis 10,16 . In this study, we performed a nonbiased analysis to assess miRNA and mRNA expression as well as ATAC-seq and ChIP-seq to investigate chromatin accessibility and TF occupancies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that muscle development is regulated by microRNAs (miR-NAs) in addition to the regulators described above. miRNAs have been reported to be involved in many biological processes, including skeletal myogenesis 6,7 and adipogenesis 8 . Muscle-specific miRNAs, including miR-1 9 , miR-133 10 , miR-206 11 , miR-208 12 , and miR-499 13 , have been considered key regulators with different targets during muscle development.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note, knockdown of miR-27b, miR-92a, miR-155, and miR-150 have all been shown to enhance browning/ beiging 6063 , one of the Ad-Tmem120a -/- pathologies. Also, miR-322, miR-15b, miR-342-5p, and miR-16 are all pro-adipogenic 6466 ; so their reduction is consistent with the pathology. Finally, miR-151-3p, miR-466f, miR-139-5p, miR-219, miR-29b, miR-25, and miR-370 are all linked to diabetes 6773 , consistent with the inability to clear glucose, insulin resistance, and elevated insulin in Ad-Tmem120a -/- mice.…”
Section: Resultsmentioning
confidence: 62%
“…35) miR-181c targeted the Akt-3 gene in cultured C2C12 myoblasts. 36) Akt-3 is a pro-survival signalling molecule in myoblasts. 37) Therefore, an intracellular increase of miR-181c in a myoblast may induce skeletal muscle dysfunction.…”
Section: Discussionmentioning
confidence: 99%